THE USE OF PAST TENSE VERBS AND ADVERBS IN STUDENTS’ RECOUNT TEXTS - Faisal Mustafa (INFERENCE: Journal of English Language Teaching, 2021)
Abstract: This study was conducted to find out the grammatical error of using Past Tense verbs and adverbs in students' recount text at private Vocational High Schools in West Jakarta. The method used in this study was descriptive analysis using qualitative data. The procedures were carried out by choosing the text from students' writing recount text, analyzing data, interpreting data, and concluding the result of the study. The result shows that 1.) There are common errors produced of using Past Tense Verb in students' recount text. The total error is 632 which the highest frequency of error happens in misformation, which consists of 375 errors or 59.33%, 2.) While the highest frequency of error in adverbs happens in omission, consisting of 21 errors or 24.07%. The findings that the students' grammatical error of using Past Tense Verbs and Adverbs in writing recount text occurred for some reasons. They are affected by the different rules between first language and target language. Moreover, it is because of insufficient students' knowledge about English grammar.Keywords: grammatical error; past tense verb; adverb; writing; recount text